2010
DOI: 10.1007/s11467-010-0003-0
|View full text |Cite
|
Sign up to set email alerts
|

Photonic crystals and microlasers fabricated with low refractive index material

Abstract: Although the investigation on photonic band gap materials has been done more than two decades, it is still a big challenge to fabricate three-dimensional photonic crystal (PC) possessing wide band gaps in visible range. In this article, we have reviewed recent progresses on fabricating the PC with low refractive index material in visible range. In contrast to the material with large refractive index, it is cheap to use low refractive index material in fabricating the PC and will be greatly beneficial for futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 135 publications
0
6
0
Order By: Relevance
“…This situation introduces a mismatch between computer based design capability of 3D aperiodic patterns and their fabrication capability. To overcome this mismatch, two useful methods have recently been introduced, namely laser holographic lithography and direct-laser-writing techniques [173]. In particular, laser holographic lithography relies on the interference of several coherent laser beams to produce a pattern that is recorded (due to photoinduced polymerization) in a photoresist material template.…”
Section: Three-dimensional Arrangementsmentioning
confidence: 99%
“…This situation introduces a mismatch between computer based design capability of 3D aperiodic patterns and their fabrication capability. To overcome this mismatch, two useful methods have recently been introduced, namely laser holographic lithography and direct-laser-writing techniques [173]. In particular, laser holographic lithography relies on the interference of several coherent laser beams to produce a pattern that is recorded (due to photoinduced polymerization) in a photoresist material template.…”
Section: Three-dimensional Arrangementsmentioning
confidence: 99%
“…The interest in PtC and PnC is to control the flow of electromagnetic and mechanical waves, respectively. Since the discovery of PtC, a fundamental milestone has been to find a structure with a complete band gap for all the directions of the space [4,5]. The limiting factor to obtain a wide photonic band gap is the contrast of the materials, higher the contrast biggest the band gap.…”
Section: Introductionmentioning
confidence: 99%
“…[6] These PC-based mirrors have low losses as compared with old metallic mirrors, specially in the infrared range. [7] Figure 1: Unit cell composed of two materials with indices n H and n L . The width of the unit cell is…”
Section: Introductionmentioning
confidence: 99%
“…[9] Additionally, even with the most recent experimental techniques it has only been possible to fabricate 3D structures with a low variation in the refractive index, typically n < 2.0. [7] This low index contrast attained in 3D PCs is a limiting factor in some applications in telecoms or near infrared range where a large range of band gap is required. [10,11] To obtain wider PBG it is desirable to increase the refractive index, different authors have reported that the width of the band gap is a function of the contrast index, the larger the better.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation